Probiotic salami with fat and curing salts reduction: Physicochemical, textural and sensory characteristics - Roselino, Mariana Nougalli [UNESP]; de Almeida, Jéssica Ferraz [UNESP]; Cozentino, Izabela Correia [UNESP]; Canaan, Josiane Marcia Maria [UNESP]; Pinto, Roseli Aparecida [UNESP]; De Valdez, Graciela Font; Rossi, Elizeu Antonio [UNESP]; Cavallini, Daniela Cardoso Umbelino [UNESP] (FapUNIFESP (SciELO), 2018)
This work was evaluated the physicochemical, textural and the sensory properties of meat products fermented with traditional or probiotic cultures with lower fat and curing salt content. Chemical composition was evaluated in T30 and instrumental texture was determined during the experimental protocol. A sensory profile evaluation was carried out using the quantitative descriptive analysis (QDA) and the acceptance test. The lowest fat content was found in the salamis processed with reduced pork fat. Texture profile analysis the F5 exhibited the lowest mean value of hardness. In QDA, the results showed that the F1 exhibited the highest mean value of regularity of the border, brightness, softness and smoked, due to the greater amount of fat in their composition. The results revealed that, in T30, there was good acceptance for all formulations and during the storage period, the mean values remained high. The consumers demonstrated a positive purchase intention for all formulations.
Keywords: Chemical composition; Probiotic salami; Sensory properties; Texture profile